Evaluating the effects of extensive reading circles on ESL learners oral communicative competence - Baharuddin Marji, Aliyah; Rafik-Galea, Shameem; Chan, Mei Yuit (Malaysian Association of Modern Languages, 2015)
Teaching communicative English is not easy, especially when many Malaysian learners are immersed within an environment that upholds Bahasa Malaysia as the medium of instruction in national schools. Additionally, English is now only taught as a subject and therefore, class time is limited to exposing learners to communication in English. Generally, English is an important second language in Malaysia and the government is concerned about the deteriorating level of competency among young learners as it prevents new graduates from being employed. This article represents part of a research which examined the effects of extensive reading circles (ERC) on ESL learners’ oral communicative competence with two intact groups of undergraduate students who registered for the oral proficiency classes. The study employed an analytical scoring to evaluate five dimensions of oral competency during subjects’ oral production interviews. Data was collected by means of pre-test and post test scores to determine the effects of ERC under two conditions scale. Results obtained from the treatment group demonstrate that subjects gained significantly on all dimensions of oral competency. Hence, the implications of these findings support the comprehensible input hypothesis and the principles underlying extensive reading and cooperative learning towards the development of oral communicative competence to ensure that learners are equipped with speaking skills pertinent for their future.